Pengaruh Model Discovery Learning terhadap Kemampuan Berpikir Kreatif Peserta Didik pada Pembelajaran IPAS Kelas V - Armawita, Natasa; Bistari, Bistari; Ghasya, Dyoty Auliya Vilda (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The implementation of IPAS learning in the classroom with a direct learning model makes students passive. This creates learning conditions that are not conducive for students to explore and discover their own knowledge, so that creative thinking skills are difficult to develop. This study aims to determine the effect of the application of the discovery learning model on students' creative thinking skills in class V IPAS learning. This research was conducted at SDN 22 West Pontianak. The method used was quasi experiment with the form of nonequivalent control group design. Sample selection with purposive sampling with data sources 33 students of class V B (experimental), and 32 students of class V A (control). The instrument used was a creative thinking ability test. The average value of the experimental class post-test results is 60.82. While the average value of the control class post-test results is 55.25. Based on the results of the calculation with the t test, tcount (2.151) > ttable (1.999) (α = 5% and dk = 63), Ho is rejected and Ha is accepted. From the calculation using effect size, the result is 0.376 with a medium category. Therefore, it can be concluded that the application of the discovery learning model affects the creative thinking ability of students in class V IPAS learning.